Crystals springing into action: metal–organic framework CUK-1 as a pressure-driven molecular spring. Issue 15 (19th March 2021) - Iacomi, Paul; Lee, Ji Sun; Vanduyfhuys, Louis; Cho, Kyung Ho; Fertey, Pierre; Wieme, Jelle; Granier, Dominique; Maurin, Guillaume; Van Speybroeck, Veronique; Chang, Jong-San; Yot, Pascal G.
Abstract : Mercury porosimetry and in situ high pressure single crystal X-ray diffraction revealed the wine-rack CUK-1 MOF as a unique crystalline material capable of a fully reversible mechanical pressure-triggered structural contraction. Abstract : Mercury porosimetry and in situ high pressure single crystal X-ray diffraction revealed the wine-rack CUK-1 MOF as a unique crystalline material capable of a fully reversible mechanical pressure-triggered structural contraction. The near-absence of hysteresis upon cycling exhibited by this robust MOF, akin to an ideal molecular spring, is associated with a constant work energy storage capacity of 40 J g −1 . Molecular simulations were further deployed to uncover the free-energy landscape behind this unprecedented pressure-responsive phenomenon in the area of compliant hybrid porous materials. This discovery is of utmost importance from the perspective of instant energy storage and delivery.